2012
DOI: 10.11646/zootaxa.3257.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary assessment of the Nactus pelagicus species group (Squamata: Gekkonidae) in New Guinea and a new species from the Admiralty Islands

Abstract: The Slender-toed Geckos (Nactus) currently have four recognized species in New Guinea, and these species divide intotwo sister clades: a pelagicus clade and a vankampeni clade (Heinicke et al. 2010). The latter contains three dwarf species.The former consists of five bisexual populations, of which numerous New Guinea populations are uncharacterized no-menclaturally and lumped under the epithet ‘pelagicus.’ This report and description of a new species of the pelagicusgroup from Manus Island in the Admiralty Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…nov. New Ireland), and a third species representing all other populations (E. schauinslandi). This latter lineage includes the population from the Admiralty Islands, which, as this island group is also part of the Bismarck Archipelago, presents an intriguing result in terms of biogeography (consistent with findings for the gecko Nactus pelagicus, Zug & Fisher, 2012). All of the new lineages proposed here, with descriptions of corollary distinguishing morphological features, will be described in another paper (Klein et al, in prep).…”
Section: Coalescent Species Delimitation and Taxonomic Conclusionsupporting
confidence: 80%
See 1 more Smart Citation
“…nov. New Ireland), and a third species representing all other populations (E. schauinslandi). This latter lineage includes the population from the Admiralty Islands, which, as this island group is also part of the Bismarck Archipelago, presents an intriguing result in terms of biogeography (consistent with findings for the gecko Nactus pelagicus, Zug & Fisher, 2012). All of the new lineages proposed here, with descriptions of corollary distinguishing morphological features, will be described in another paper (Klein et al, in prep).…”
Section: Coalescent Species Delimitation and Taxonomic Conclusionsupporting
confidence: 80%
“…The similar timing for these initial radiations of E. impar and E. cyanura could be due to the relative stability of the Pacific region since the early to mid-Pliocene; most island groups throughout central and eastern Pacific have been emergent or geologically stable since at least this era (Hall, 2002;Neall & Trewick, 2008). Human movements, from early settlers of the Polynesian region to American and Japanese troops during World War II, most likely have played a key role in producing the current extant ranges of E. impar and E. cyanura (as found for other Pacific squamates; Austin et al, 2011;Zug & Fisher, 2012;Tonione et al, 2015), and have further contributed to the low degree of variability observed between most of the sampled populations.…”
Section: Rapid Radiation: Human-mediated or Natural?mentioning
confidence: 91%
“…Because no taxonomic studies had yet been performed, pelagicus was applied to all, and by default, this group of cryptically brown-colored Nactus became the pelagicus complex or species group. This usage persists even though we now know it is a polyphyletic group (Heinicke et al, 2010;Zug and Fisher, 2012). Herein, I use "Nactus pelagicus complex" for all Pacific area Nactus populations with a mean SVL ≥ 42 mm that possess longitudinal rows of dorsal tubercles on the trunk.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent molecular phylogenetic analysis (Zug and Fisher, 2012) with an even broader geographic sampling of the N. pelagicus group suggests a broader (more inclusive) pelagicus group that includes all dwarf species. Their mitochondrial DNA phylogram closely matches the one in Heinicke et al (2010).…”
Section: History Of Discoveries In Australo-pacific Nactusmentioning
confidence: 99%
See 1 more Smart Citation